Involvement of child labour in aquaculture activities in Mymensingh district, Bangladesh - Ferdousi, Khaleda; Faruk, Md Ali Reza (Research in Agriculture Livestock and Fisheries, 2016)
A study was conducted to know the involvement of child labour in various aquaculture activities in two upazilas namely Trishal and Muktagacha in Mymensingh district. Data were collected during December 2013 to April 2014 from 35 aqua farms having 492 workers, among them 100 (20.33%) were identified as child labour. All the child workers were interviewed through structured questionnaire. Feed preparation, feeding, sorting and grading of fish and rearing of fry in ponds were the major activities where maximum child labours were found to involve. It was observed that the main cause of children to involve such activities was poverty and dropped out from school. Overall 71% child labour worked to support their family and 48% recruited according to their parents decision. About 55% child labour worked more than 60 hours per week and few (19%) of them got break during working hours. The child workers had very limited freedom in their working area and found to be abused mentally and physically to some extent by the farm owners. The children were also found associated with various hazardous works like contact with chemical, long time work in water logged area and lifting heavy weight. Generally, the farm owners recruited child labour in their farms as cheap worker and majority (77%) of the farm owners have no idea about the current laws of recruitment of child labour. More studies are needed to establish the extent of child labour in overall aquaculture sector of Bangladesh. It is also important to implement effectively the national minimum age legislation for aquaculture. Res. Agric., Livest. Fish.3(3): 433-442, December 2016